1998
DOI: 10.1016/s0954-6111(98)90100-7
|View full text |Cite
|
Sign up to set email alerts
|

Medical thoracoscopy, results and complications in 146 patients: a retrospective study

Abstract: In a retrospective study the results of medical thoracoscopy in 147 patients were reviewed; 136 of the patients had pleural effusion and 11 patients had diffuse pulmonary infiltration. All the pleural exudates were initially screened three times successively and found to be sterile and without tumour cells. All thoracoscopies were performed with local anaesthesia, with the 'open technique', and nine different doctors performed the thoracoscopies. The overall diagnostic sensitivity was 90.4%. The results demons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
62
2
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 117 publications
(72 citation statements)
references
References 7 publications
7
62
2
1
Order By: Relevance
“…In the current study, the diagnosis of tuberculous pleural effusion was established by the presence of Mycobacterium tuberculosis in pleural biopsy specimen, or by demonstration of caseating granulomas and/ or epithelioid cell granulomas in pleural tissue with no evidence of other granulomatous diseases. As expected, in the present study, we observed that 40.0% (333/833) of the patients who underwent MT were confirmed to suffer from tuberculous pleural effusion, which was much higher than the 5.9% reported in the study from New Zealand [12] , the 5.6% from the United Kingdom [14] , the 3.2% from Spain [22] , the 2.7% from France [13] , the 2.0% from Denmark [23] , and even the 0% from the United States [24] .…”
Section: Discussionsupporting
confidence: 80%
“…In the current study, the diagnosis of tuberculous pleural effusion was established by the presence of Mycobacterium tuberculosis in pleural biopsy specimen, or by demonstration of caseating granulomas and/ or epithelioid cell granulomas in pleural tissue with no evidence of other granulomatous diseases. As expected, in the present study, we observed that 40.0% (333/833) of the patients who underwent MT were confirmed to suffer from tuberculous pleural effusion, which was much higher than the 5.9% reported in the study from New Zealand [12] , the 5.6% from the United Kingdom [14] , the 3.2% from Spain [22] , the 2.7% from France [13] , the 2.0% from Denmark [23] , and even the 0% from the United States [24] .…”
Section: Discussionsupporting
confidence: 80%
“…Subcutaneous emphysema, localized infection of the incision site, hypotension, fever, atrial fibrillation during the procedure are minor; empyema, hemorrhage, tumor seeding in port site, bronchopleural fistula, pneumonia, prolonged air-leak and re-expansion pulmonary edema are the major complications reported from various studies (11). The complication rates in our study were similar to the literature; the post-operative hospitalization period was shorter in our study (Table 3) (4,8,(12)(13)(14)(15). The most common complication was subcutaneous emphysema; however, these patients had similar hospitalization days compared to the rest of the patients.…”
Section: Discussionsupporting
confidence: 86%
“…The main one is the fact that we used hypoxemia as a surrogate marker for morbidity and mortality instead of peri-interventional mortality as the endpoint of the study. However, due to the rarity of lethal complications in this setting (0.05-1%) [1,32,33], the estimated sample size for a study identifying a difference in mortality of 0.5% between the groups would be over 15,000 patients. Even a composite endpoint including relevant complications (incidence less than 3%) and tolerating a 2-fold higher incidence of adverse events (6%) would require over 1,500 patients.…”
Section: Discussionmentioning
confidence: 99%